INSTAGRAM MEDIA CONTENT ANALYSIS @BICKLEYFLORIST FLOWER BOUQUET BUSINESS AS PROMOTIONAL MEDIA - Amalia Nurdiana Putri; Nur Maghfira Aesthetika (PT. Antis International Publisher, 2024)
General Background: In the digital age, social media platforms, particularly Instagram, have become essential tools for businesses to enhance their marketing efforts and engage with consumers. Specific Background: This research focuses on the Instagram account @bickleiyflorist, aiming to analyze how its content aligns with the principles of Social Media Marketing (SMM) to promote its flower bouquet business. Knowledge Gap: While numerous studies address social media marketing strategies, there is a lack of detailed analyses regarding specific content dimensions and promotional tactics utilized by individual accounts within niche markets such as floristry. Aims: The primary aim of this study is to investigate the social media content of @bickleiyflorist and its effectiveness in engaging audiences and driving sales. Results: Through descriptive qualitative research, data was collected from Instagram posts between January and July 2024. The findings reveal that @bickleiyflorist's content reflects five key dimensions of SMM: Entertainment, Interaction, Trendness, Customization, and Word of Mouth communication. Additionally, the account employs various promotional strategies, including visually appealing photos and videos, informative captions, and relevant hashtags to enhance content discoverability. Novelty: This research provides a focused analysis of how a specific Instagram account in the floristry sector leverages social media marketing dimensions and promotional strategies, offering insights that can be applied to similar businesses. Implications: The findings demonstrate that @bickleiyflorist effectively uses Instagram as a promotional platform, highlighting the importance of engaging and informative content paired with strategic marketing tactics to capture audience attention and boost sales. This study contributes to the broader understanding of effective social media practices in niche markets.